Ecologia de taxocenose de anfíbios anuros em poças temporárias na caatinga - Protázio, Arielson dos Santos (2012)
In theroy, the influence of phylogeny in community structure implies that phylogenetically close species may show similar characteristics determined by their evolutionary history. In a fine scale, this is useful to identify processes of microevolution. We used phylogenetic and ecological data to investigate the determinant factors of the relationships among 15 anuran species in temporary ponds in Caatinga. Phylogenetically close species used the same categories of microhabitat, but they differed in usage proportion. Considering diet, overlap values were high in phylogenetically related species and these species tended to form concise groups. Analysis based on null models indicated no significant values of overlap in microhabitat usage and diet composition, showing that competition is unlikely to regulate assemblage structure. Species belonging to the same phylogenetic lineage occupied the same morphological space, suggesting that morphometry may be a conservative trait; however, some close related species have diverged in this pattern. The joint observation of microhabitat usage, diet composition, and morphology indicated the existence of similarities among phylogenetically related species. Canonical Phylogenetic Correlation Analysis revealed the presence of niche phylogenetic conservatism in microhabitat usage in Hylidae and Leptodactyliformes basal dichotomy and in diet composition of the Physalaemus genus. In this work, it is considered that the phylogenetic relationships influence assemblage structure. However, the observation of differences in resource usage among closely related species and similarities among unrelated species suggests the existence of ecological factors acting at some moment of the evolution of these organisms.